2006
DOI: 10.1007/s00198-005-0027-4
|View full text |Cite
|
Sign up to set email alerts
|

The effect of age and bone mineral density on the absolute, excess, and relative risk of fracture in postmenopausal women aged 50–99: results from the National Osteoporosis Risk Assessment (NORA)

Abstract: At any given BMD, not only the absolute fracture risk but also the excess fracture risk increased with advancing age. Relative risk of fracture for low bone mass was consistent across all age groups from 50 to 99 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
133
0
10

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 231 publications
(151 citation statements)
references
References 49 publications
8
133
0
10
Order By: Relevance
“…38,39 Studies on physical activity for CTIBL in women with breast cancer P Hadji osteoporosis prevention have shown diverse results on BMD. 40,41 A case-control study showed a delay in the loss of BMD in 66 pre and postmenopausal women with BC using either aerobic ( À 0.8%) or weight training ( À 4.9%) compared with controls. 42 In the current guidelines (ESMO, DVO), the level of evidence and the degree of recommendation arestill low (4/C).…”
Section: Practical Aspects Of the Treatment Of Ctiblmentioning
confidence: 99%
“…38,39 Studies on physical activity for CTIBL in women with breast cancer P Hadji osteoporosis prevention have shown diverse results on BMD. 40,41 A case-control study showed a delay in the loss of BMD in 66 pre and postmenopausal women with BC using either aerobic ( À 0.8%) or weight training ( À 4.9%) compared with controls. 42 In the current guidelines (ESMO, DVO), the level of evidence and the degree of recommendation arestill low (4/C).…”
Section: Practical Aspects Of the Treatment Of Ctiblmentioning
confidence: 99%
“…Additional data from the NORA study indicate that at least 45% of fractures occur in women with two or more fracture risk factors. It is important to note that our estimates of fracture prevention are based on fracture risk in healthy women (Siris et al, 2006) and might therefore underestimate the true protective effect of bisphosphonates in the BC setting.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, LS osteoporosis was also more prevalent in postmenopausal patients with ER þ vs ER -BC (3.1 vs 1.3%; Figure 2B). The prevalence of clinical factors associated with increased fracture risk independent of BMD is presented in Table 2 (Cummings et al, 1995;Kanis et al, 2005Kanis et al, , 2007Siris et al, 2006;Hadji et al, 2008). Except for age (465 years), history of smoking (B28%), and AI therapy (B30%), each validated fracture risk factor had low prevalence (o6%) among postmenopausal patients with ER þ BC; however, 44.4% of these patients had T-scores oÀ1.5.…”
Section: Prevalence Of Osteopenia Osteoporosis and Fracture Risk Famentioning
confidence: 99%
See 2 more Smart Citations